Empowering Young Women Through the Healthy Without Anemia Movement in Taman Bondowoso Village: Pemberdayaan Remaja Putri Melalui Gerakan Sehat Tanpa Anemia di Desa Taman Bondowoso - Aditya Faradina Salsabilla; Anis Fila Klaudia; Fatimatus Zahroh; Adhyasta Yuda Adrianto; Irfan Maulana; Yudha Nurdian (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Adolescent girls are at higher risk of anemia due to an increased need for micronutrients such as iron, but also prone to iron deficiency caused by menstrual blood loss. Iron deficiency anemia could be harmful for teenage girls because it significantly affects cognitive and physical abilities, and results in giving birth to stunting babies if it is not well treated. In this counseling activity to prevent anemia for adolescent girls in Taman Village, Bondowoso, they were also provided with training in making brownies from jackfruit seeds. Interest in entrepreneurship followed by awareness of the dangers of anemia in adolescent girls can be increased through this activity. Parameters for assessing the success of this program are done by filling out questionnaires by participants. The results obtained indicate that the “SETIA (Sehat Tanpa Anemia)” activity program is beneficial for participants who take part in it.